For all mankind. Season two [videorecording (Blu-Ray)] - Moore, Ronald D.; Wolpert, Matt; Nedivi, Ben; Russo, Jeff, 1969- (Sony Pictures Home Entertainment, 2026)
Season two picks up in 1983, the height of the Cold War, with tensions between the United States and the USSR at their peak. The Department of Defense has moved into Mission Control, and the militarization of NASA becomes central to several characters' stories: some fight it, some use it as an opportunity to advance their own interests, and some find themselves at the height of a conflict that may lead to nuclear war.